The Intersection of Problems, Policy, and Politics: The Adoption of an HPV Vaccine School-Entry Requirement in Puerto Rico. (April 2021) - Vázquez-Otero, Coralia; Daley, Ellen M.; Vamos, Cheryl A.; Romero-Daza, Nancy; Beckstead, Jason; Martinez Tyson, Dinorah
Persistent human papillomavirus (HPV) infections can cause cancer (e.g., cervical/vaginal/penile/anal/oropharyngeal). The HPV vaccine prevents cancer, yet U.S. vaccination rates remain low. We explored sociopolitical factors in the adoption of Puerto Rico's HPV vaccine school-entry requirement. Multiple streams framework explains how the intersection of problems, policy, and politics streams influence policy adoption. Policy entrepreneurs work on joining these streams. Interviews ( n = 20) were conducted with stakeholders (e.g., physicians/researchers/nonprofit organizations' leaders). Data were analyzed using applied thematic analysis. High incidence of HPV and HPV-related cancers in Puerto Rico were indicators of problems. Focusing events included Rhaiza's case and the HPV-Advisory Panel Report. During summer 2017, a policy window opened; the Department of Health (DOH) adopted the requirement in summer 2018. Stakeholders discussed policy initiatives. Political turnover positively influenced the process. Policy entrepreneurs created an extended period of intersection resulting in the adoption of the requirement. Findings can inform policy initiatives to improve HPV vaccination rates and reduce HPV-related cancers.